Strategi Kolaborasi Erigo dengan JKT48 dalam Penjualan Secara Live Streaming pada Online Marketplace Shopee - Faris Saputra Dewa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Sales activities through online marketplaces today are not just about making product visuals, product titles, and descriptions as attractive as possible. The presence of the live streaming feature can be utilized by sellers to reach more buyers with faster and more intimate interactions. Erigo is one of the sellers who utilizes the Shopee Live live streaming feature provided by Shopee. Erigo collaborated with the idol group JKT48 in various forms of promotion, one of which was by involving JKT48 members in live streaming activities on Shopee Live. There was an increase in the number of viewers and turnover obtained by Erigo when JKT48 members were actively involved in live streaming activities through Shopee Live. The popularity of JKT48 and fan fanaticism are important in the success of the collaboration carried out by Erigo and JKT48.